Selisik Tindak Pidana Kenakalan ‘Perundungan Fisik’ Anak Di Lingkungan Sekolah Berdasarkan Aspek Hukum Pidana - Meida Adita Rahma; Surastini Fitriasih (Jurnal USM Law Review)
The purpose of this study is to analyze criminal acts related to the phenomenon of bullying among children in school environments, focusing on the delinquency of children aged 12-18 years in the form of physical violence such as bullying. This research particularly emphasizes the role of educators in handling bullying, which impacts the understanding of both the physical and psychological effects of bullying. This study uses a normative research method. Bullying that is considered a 'joke' can have a domino effect and have fatal consequences. Education by educators and parents, counseling or socialization, and the role of the community are very important to prevent and overcome bullying. The research findings reveal that bullying constitutes a criminal offense categorized within the realm of violence against children, with various underlying factors contributing to its occurrence. It is noteworthy that approximately 341 victims of physical bullying, involving severe assault resulting in serious injuries or fatalities, have been documented.